2022
DOI: 10.1002/hsr2.840
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and perception of breast cancer among women of reproductive age in Chattogram, Bangladesh: A cross‐sectional survey

Abstract: Background and Aims: Breast cancer is the second leading cause of cancer death in women worldwide. The significantly higher mortality rate has been considered due to poor knowledge of women, delay in diagnosis, and initiation of treatment.Therefore, this hospital-based cross-sectional study aimed to understand the knowledge and perception of women with breast cancer in Bangladesh.Methods: Data was collected using a questionnaire-based interview from 357 women aged 15-49 years attending two tertiary care hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Moreover, a study conducted by Mehejabin et al sought to examine the level of knowledge regarding various aspects of breast cancer among women in Bangladesh. The findings revealed that a majority of the participants, exceeding 50%, possessed a limited understanding of the risk factors associated with breast cancer, indicating a significant lack of knowledge [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a study conducted by Mehejabin et al sought to examine the level of knowledge regarding various aspects of breast cancer among women in Bangladesh. The findings revealed that a majority of the participants, exceeding 50%, possessed a limited understanding of the risk factors associated with breast cancer, indicating a significant lack of knowledge [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the study conducted by Mehejabin et al indicate that a considerable proportion of women hold the belief that breast cancer can be detected at a young age. Furthermore, the participants held the belief that early diagnosis of the disease could lead to its potential cure [ 53 ]. The aforementioned findings align with the results obtained from a research study carried out at Dhaka Medical College Hospital in Bangladesh, wherein 51.43% of female participants indicated that early detection of breast cancer leads to a potential cure [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…In terms of employment, the patient was known to be a housewife. According to research (Mehejabin & Rahman, 2022), up to 76.2% of women are housewives. The high rate in this position is attributable to a lack of understanding of the breast cancer risk factors.…”
Section: Respondent Characteristicsmentioning
confidence: 99%
“… 9 However, screening practice and its associated factors among Bangladeshi women are yet to be established by epidemiological studies. A few studies reported poor knowledge and awareness of breast cancer among Bangladeshi women 10 , 11 , 12 , 13 , 14 However, these studies were on either hospital‐based or specified group. Little evidence is available on breast cancer screening awareness and its perceived barrier by the women of this region with poor awareness on breast cancer who seek treatment at the later stage of breast cancer.…”
Section: Introductionmentioning
confidence: 99%